Peranan Gereja dalam Menghambat Laju Pertumbuhan Pemakai Narkoba - Simon Simon (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2019)
Indonesia is a country that is fertile ground for drug trafficking carried out by domestic dealers and drug dealers internationally. The rise of drugs today causes victims to die every day. President Jokowi came to state that Indonesia was on the verge of a